A A Text Structure Analysis of Nadiem Makarim’s Speech on Teacher’s Day on 25 November 2021 - Linda Lestari, Linda Lestari; Rohmah, Ainur; Hadziq Fikri, Arief; Muklas, Muhamad (ENJEL: English Journal of Education and Literature, 2022)
This study concerns with an A Text Structure Analysis of Nadiem Makarim’s Speech on Teacher’s Day on 25 November 2021. The objective of the study is to know the types of text structure used in Nadiem Makarim’s Speech on Teacher’s Day on 25 November 2021. The writer used descriptive qualitative method to know the objective of the study that is describing of text structure used in Nadiem Makarim’s Speech on Teacher’s Day on 25 November 2021. The technique of collecting the data are by searching for the script, searching for the video and then downloading the script and the video. The technique of analyzing the data are data reduction, display the data and the last is conclusion drawing/verification. Based on the the findings, the writer found macrostructure, suprastructure and microstrucure. In macrostructure, the theme of the Nadiem Makarim’s Speech is generally talking about the struggle of teachers in Indonesia in a pandemic situasion. Then in suprastructure, the scheme of the speech consisted of opening, content and closing. Finally in the microstrucure, the semantic aspect could be found in detail.